Hubungan Tingkat Pengetahuan Ibu Tentang Gizi Dengan Status Gizi Balita - Naktiany, Wayan Canny; Yunita, Lina; Rahmiati, Baiq Fitria; Lastyana, Wiwin; Jauhari, M. Thonthowi (Nutriology : Jurnal Pangan, Gizi, Kesehatan, 2022)
The description of the nutritional status of children under five represents the degree of public health. Indonesia is experiencing multiple nutritional problems, namely the problem of undernutrition has not been completely resolved, the problem of overnutrition (obesity) appears. Nutritional status is influenced by unbalanced energy intake and infectious diseases. This is due to the level of education, knowledge, parenting patterns that are inappropriate and bad environmental sanitation. The biggest problem faced by the community is the low level of knowledge and skills of mothers about nutrition. This study aims to determine the relationship between mother's level of knowledge about nutrition and the nutritional status of children under five in Lembah Sari Village, West Lombok. This type of research is an observational study with a cross sectional approach. The sample in this study were mothers who have toddlers (aged 6-60 months) and their babies, totaling 55 people. Sampling technique with cluster random sampling. The results obtained based on the chi square test showed that there was a significant relationship between the mother's level of knowledge about nutrition and the nutritional status of children under five in Lembah Sari Village, West Lombok Regency with a p-value of 0.015. The results of the analysis of the relationship between the level of knowledge related to nutrition and the nutritional status of children under five, that was found that 7 respondents with less knowledge had poor nutritional status (46.67%). Two respondents with good knowledge had poor nutritional status (5%), while 8 respondents with poor knowledge had good nutritional status (53.33%) and 38 respondents with good knowledge had good nutritional status (95%). Conclusion: there is a relationship between the mother's level of knowledge about nutrition and the nutritional status of children under five in Lembah Sari Village, West Lombok Regency. Suggestion: it is necessary to add other variables that can affect the level of knowledge of mothers and caregivers regarding the nutritional status of children under five years.